Pengaruh Sense of Belonging dan Lingkungan Kerja Terhadap Employee Engagement Pada Karyawan PT Jago Bahasa Inspira - Catri Krista, Berliana; Syahputra, Erwin (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
This study discusses the effect of a sense of belonging and the work environment on employee engagement at PT. Jago Bahasa Inspira employees. This study aims to determine and explain the results of the influence of a sense of belonging and the work environment on employee engagement at PT. Jago Bahasa Inspira employees. The sample of this research is all employees of PT. Jago Bahasa Inspira who work in an office with a total of 59 employees. The sampling technique uses Non-Probability Sampling, namely saturated sampling. The analysis technique used is the classical assumption, multiple linear regression. The results of this study are that there is a positive and significant sense of belonging to employee engagement with a significant value of 0.000 <0.05. There is a positive and significant effect of the work environment on employee engagement with a significant value of 0.000 <0.05. There is a simultaneous influence of sense of belonging and work environment on employee engagement with a significant value of 0.000 <0.05.